Developing Socioentrepreneurship for Students tt The University - sajidan sajidan (Jurnal Pendidikan Dasar, 2019)
Abstract: Inevitably, entrepreneurs contribute significantly in the economic development of a state, due to its limited resources to provide welfare for its citizens. Entrepreneurs as agents of change require a set of personal characteristics to identify and pursue opportunities, to think creatively in developing new innovative solutions or approaches, and to possess fortitude to take risk when challenges and barriers arise in creating beneficial changes for society. Grounded in the same elements, the term of business entrepreneurs is now shifted to social Entrepreneurs, which aims at creating values and benefits that have significantly massive and sustainable impact. To achieve this, social entrepreneurship requires changes in education. Ideally, the characteristics of entrepreneurs should be introduced in the early stage of education. It is important to raise students’ willingness to adopt new ideas, to take initiatives, to solve problems, and develop empathy. For that reason, university plays significant roles to integrate the idea that students can be the agents of change by developing comprehensive standard of curriculum and methods of learning, and providing the opportunity to learn directly from the first hand. Keywords: Social entrepreneurship, agents of change, students, classroom, university